Aging cochleas in the F344 rat: morphological and functional changes - Buckiová, Daniela; Popelář, Jiří; Syka, Josef (Experimental gerontology, 2007)
The Fischer 344 rat strain has been frequently used as an animal model of rapid aging. The present study was aimed at evaluating the incidence of apoptotic cells in the inner ear of 20-24-month-old F344 rats and to correlate it with cochlear function using otoacoustic emissions. Staining with cresyl violet and the enzymatic labeling (terminal deoxynucleotidyl transferase, TdT) of fragmented DNA revealed large numbers of apoptotic cells in the marginal and basal layers of the stria vascularis and in adjacent cells of the spiral ligament. The amplitudes of distortion products otoacoustic emissions (DPOAEs), which reflect functional state of the outer hair cells, were significantly reduced or totally absent in these animals. In contrast to old F344 rats, no marked DPOAE amplitude reduction and smaller numbers of apoptotic cells were found in young 4-month-old F344 rats or in aged 24-28-month-old Long Evans rats. The accumulation of apoptotic cells, mainly in the basal layer of the stria vascularis and in adjacent cells of the spiral ligament, leads to a detachment of the stria vascularis from the spiral ligament and results in the impairment of outer hair cell function. This specific type of strial deterioration suggests that aged F344 rats can serve as an animal model of strial presbycusis.
Keywords: Animals; imunohistochemie; Rats; Financing, Organized; Hearing; fragmentace DNA; Cell Death; potkani inbrední F344; Rats, Inbred F344; Immunohistochemistry; stárnutí; modely u zvířat; apoptóza; DNA Fragmentation; Models, Animal; Aging; Cochlea; zvířata; Species Specificity; kochlea; druhová specificita; financování organizované; krysa rodu Rattus; Apoptosis; sluch; buněčná smrt